2020
DOI: 10.31101/jkk.306
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan pengetahuan ibu tentang perawatan bayi berat lahir rendah (BBLR) dengan kenaikan berat badan bayi

Abstract: Abstrack: The objective of the research is to know the correlation between mother’s knowledge about the treatment of LBW and baby’s weight gain at RSUD Wates in 2016. This research is a correlative-descriptive research using cross sectional time approach. The population of this research was mothers who have LBW, and 59 respondents were selected using quota sampling. This research uses questionnaire to get the data and chi-square for analysis test. Test the validity of using Product Moment correlation and Cronb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
1
1
0
5
Order By: Relevance
“…The results of this study indicate that there are differences in parental readiness in caring for LBW before and after being given LBW care education and there is an effect of providing LBW care education on parental readiness to care for LBW, in line with the research results which mothers' knowledge of good LBW care can increase the baby's weight (Ningsih, Suryantoro & Nurhidayati, 2017). Mothers with LBW are at risk of experiencing psychological stress and postpartum depression.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The results of this study indicate that there are differences in parental readiness in caring for LBW before and after being given LBW care education and there is an effect of providing LBW care education on parental readiness to care for LBW, in line with the research results which mothers' knowledge of good LBW care can increase the baby's weight (Ningsih, Suryantoro & Nurhidayati, 2017). Mothers with LBW are at risk of experiencing psychological stress and postpartum depression.…”
Section: Discussionsupporting
confidence: 76%
“…The results showed that the mother's knowledge about the implementation of low birth weight care at home was still in the low category. Mother has less knowledge in maintaining temperature and warmth of 75.56% (Ningsih, Suryantoro & Nurhidayati, 2017).…”
mentioning
confidence: 99%
“…Selain bermanfaat sebagai termogulator, KC juga meningkatkan ikatan kasih sayang antara ibu dan bayi agar berat badan bayi bertambah. KC juga memudahkan pemberian nutrisi, mencegah infeksi dan menekan biaya perawatan dini (Ningsih, Suryantoro and Nurhidayati, 2020). PT yang diserahkan ke KMC menunjukkan kualitas pergerakan yang lebih tinggi dan skor yang lebih rendah dalam kaitannya dengan tanda-tanda stres.…”
Section: Manfaat Untuk Fisik Bayiunclassified
“…Pengetahuan yang memadai tentang kehamilan, persalinan, asi eksklusif, perawatan bayi dan balita menjadi dasar bagi ibu untuk melakukan upaya peningkatan kesehatan. Hasil penelitian (17) menyebutkan bahwa pengetahuan ibu tentang perawatan BBLR yang baik dapat meningkatkan berat badan bayi. Pengetahuan ibu yang baik juga memiliki hubungan yang signifikan dengan pemberian MPASI dini pada bayi usia kurang dari enam bulan (18) .…”
Section: Pembahasanunclassified